A comparison of electrical activity of serratus anterior and upper trapezius muscles and scapular symmetry in three fields of shooting - Safoura Heshmati; Hassan Daneshmandi; seyyed Hosseein Hosseini (Islamic Azad University, Hamedan Branch, 2018)
Objective: The purpose of the present study was to compare the serratus anterior and upper trapezius muscles activities in the shoulder abduction and scapula symmetry position between three shooting fields including archery, pistol and air rifle. Methods: Twenty-four available shooters of 20-40 years old with more than 3 years of professional training history were participated in this study. The electrical activity of subjects in during 60 and 90 degree abduction with dominant hand were evaluated by using surface electromyography and scapular symmetry position by using Modified Lateral Scapular Slide test. Data were analyzed by independent t-test, ANOVA. Results: In both positions of 60 and 90 degree abduction, the activity of the serratus anterior muscle in archery group was significantly more than the pistol and air rifle ones (P< 0.05). However, in the activity of the upper trapezius muscle didn’t indicate any significant difference in three groups (P> 0.05). There were significant differences between distances of two lower scapular angles from the vertebral column in positioning of the hand on the hip in air rifle, and in positioning of the hand in 90 degree elevation, in archery and pistol groups (P< 0.05). Also there were significant differences in the scapular symmetry in positioning of the hand on the hip, and in 90 degree elevation, between archery and rifle groups, and between rifle and pistol groups (P< 0.05). Discussion and conclusion: The different positioning of hand and shoulder in the different fields shooters as the dominant postures during exercises and competitions, can be one of the most important causes of the difference in muscles electrical activity and scapular symmetry among these groups.